Penatalaksanaan Fisioterapi Pada Kasus Post Stroke Hemiparese Dextra DI RST. DR. Soedjono Magelang - NASTITI, Iradian; Totok Budi Santoso, S.Fis, M.Ph (2014)
Background : Stroke is a disease with acute functional disorders, focal and global, which is a result of the interruption of blood flow to the brain is disrupted due to bleeding or obstruction with symptoms and signs the appropriate part of the brain that is affected, which can recover completely, cured with a disability, or can also result in death. In post stroke patients are usually encountered several problems such as abnormalities tone ( placid and spastic ), coordination and balance, loss of normal postural reflex mechanism and abnormalities sensomotoris due to complications. Objective : To determine the benefits of Infra red modalities , therapeutic exercise , and walking exercise in reducing spasticity, increase muscle strength , improve improve range of motion, and improve functional ability. Method : Physiotherapy methods used in the case that the infra red modalities, exercise therapy using the PNF and evaluation with spasticity measurement methods (Asworth Scale), measurement of functional activity (Indeks Barthel) and measurement of motion (Goneometer). Results : After 6 times the therapeutic results obtained on the limb spasticity assessment of shoulder dextra T1: 1 to T6: 0 , elbow T1: 2 to T6: 1+ , ankle T1: 2 to T6: 1 and increased functional activity of scores T1: 87 ie moderate dependence, be balanced T6: 94 ie mild dependence and improved gait. Conclusion : Giving Infra red but used as a reduction of pain can also be used for warming up before exercise provision in order to get maximum results, exercise therapy with PNF method can reduce the value of spasticity and maximize functional activity post stroke patients , practice walking with Gait control can restore the pattern street post stroke patients due to train coordination and balance that could worsen during the stroke.